لێكچوون و جياوازى مۆرفيمى ڕێژه‌يى له‌ كرمانجيى خواروو و كرمانجيى سه‌روودا - كريم, پ. ى. د. عمر محمود; احمد, م.هه‌ڵدێر بهاءالدين (Sulaimani Journal for Humanities, 2023)
This research is in titled (The similarities and differences between aspect in Central Kurdish and Northern dialects), It is an attempt to discuss an important Subject in language which is (Aspect), in this research aspect and it’s type have been clarified especially grammatical aspect since this aspect deals with the duration of verb and declares the completion and incompletion of it. Aspect is available in most of the languages and Kurdish language is the one that aspect plays a great role. This phenomena is valid in both Central and Northern dialects and organized systematically, however Kurdish language deals with tense more than aspect but it doesn’t mean that there is no aspect at all . There are differences and similarities according to form and inflection in both dialects. The researcher declares that aspect clearly affects the duration of verbs, and also briefly the difference between tense and aspect has been clarified since they are two different conceps, aspect deals with the internal temporal situation while tense deals with external temporal situation.